Uganda : Technical Assistance Report-Strengthening Cash Management. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses measures to strengthen cash management in Uganda. It recommends establishing a high-level cash management committee to provide the necessary authority to the Cash Policy Department (CPD) in maintaining its relationships, in constantly improving the cash flow forecasts, and in operating active cash management transactions. In the medium term, when cash flow forecasting has gained sufficient accuracy, the CPD must prepare for active cash management operations which will consist of short-term borrowing and investment. An appropriate cash buffer level also needs to be calculated which will define the necessary money market transactions to smooth government cash operations.